Strategic Analysis Of Airasia Berhad\'s Ability To Sustain Its Competitiveness As A Leading Low Cost Carrier In Asia Pacific - Poh , Phaik See (2008)
This thesis seeks to answer this question. It is the entire case study of AirAsia incorporating the findings in Part I - industry analysis and its key trends with focus on how low cost carriers, and Part 2 - analysis of the AirAsia\'s corporate structure and developments, to conduct a strategic analysis of AirAsia Berhad\'s ability to sustain its competitiveness as a leading low cost carrier in Asia Pasific.